Herbicide Adoption Pattern of Cotton Farmers in Vidarbha - N.M. Kale, D.M. Mankar and P.P. Wankhade, (Indian Journal of Extension Education, 2018)
A systematic extensive survey of 240 cotton growers on herbicide adoption was conducted in Vidarbharegion of Maharashtra during 2013-2014. The study revealed that 48.17 per cent cotton growers had appliedherbicides during 2013-14 for control of weeds in cotton crop. Knowledge about recommended per hadoses of herbicide is not known to 62.50 per cent farmers. Overall 52.90 per cent farmers had medium levelof knowledge about selected 15 herbicide application practices for cotton crop. Out of the total 118 (48.17%)herbicide adopters in cotton 25 (21.18%) farmers applied only single spray of post-emergence/selectiveherbicide, followed by 30.52 per cent herbicide adopter farmers applied two applications of herbicides,first applied post-emergence/selective herbicides and in second application they have used glyphosate asnon-selective herbicide and remaining 48.30 per cent farmers had applied single spray of ‘glyphosate’ at50 DAS in cotton. Majority herbicides users applied the recommended dose in cotton crop. Out of the total 118 (49.17%)herbicide adopters majority 101 (85.60%) farmers have used knapsack sprayer in cotton. Cent percent(100%) farmers have not done the calibration of sprayer pump. Out of the total 118 (49.17%) adopters 93(78.81%) farmers have used non-selective herbicides in cotton and out of them majority (88.17%) farmersused the hood for protective application. Out of total 118 (49.17%) adopters only 27.97 per cent farmersused recommended 500 liters of water /ha in cotton crop. Overall cotton farmer’s choice was Pyrithiobacsodium (Hitweed) and glyphosate. Over half (62.50%) of the farmers expressed that they are not gettingthe proper information about herbicide applications from extension functionaries of the Government, hencethe State Department of Agriculture should organize regular training/workshops, demonstrations, preparationand distribution of printed material about use of herbicides before sowing season with the expertise ofSAU scientists so that cotton cultivators in Vidarbha will get technical knowledge for effective use ofherbicides.